Financial Instability and the State of Environmental Quality in Nigeria - Adam, Ibrahim Muhammad; Jakada, Aminu Hassan; Ahmad, Ali Umar; Danmaraya, Ismail Aliyu; Marmara, Abdullahi Daiyabu; Abubakar, Abdul-azeez (International Journal of Business, Economics and Management, 2021)
The study aims to look at the relationship between environmental quality and financial instability in Nigerian over the period of 1970 to 2019 respectively. The Autoregressive Distributed Lag (ARDL) model is used in estimating the short-run as well as the long-run relationship between financial instability and the quality of the environment. The results of the study reveal that financial instability has a significant and positive impact on CO2 emissions, implying that financial instability is lowering the quality of environment in Nigeria. In addition, consistency and strength are verified by the application of numerous tests of diagnostic. The research introduces new insights that would not only be of benefit in advancing prevailing research but may also be of specific concern to policymakers in the financial sector of the country and its starring role in enhancing the quality of the environment. The results recommend that to prevent financial instability and its effect on environmental degradation in the light of policy consequences, financial sector reforms should be implemented with great caution.